Libraries, books and readings through COVID-19 - Blanco, Nancy (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2020)
This Editorial analyzes the situation of COVID-19 from a diachronic perspective inthe field of books, libraries and education. The social aspects and the characteristics in which the information in the media occurs are expressed. The library space is seen as a physical and virtual environment and teaching is described in its strategies to adapt to the new environment in the Internet era. In this context, conversation is seen as the common meeting place for enunciation and validation. These scenarios are exposed in a changing reality and allow an almost photographic exhibition to denote what happened in the course of the pandemic from the discipline viewpoint.